The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/2156759x211018659
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology Characteristics as Predictors of School Climate Among Hispanic/Latinx Students

Abstract: We used multiple regression analyses to explore ways that hope, resilience, and happiness influenced school climate among 380 Hispanic/Latinx students. The results suggested that hypothesized protective factors explained school climate to a greater degree among middle school participants ( R 2 = .23) when compared to those in high school ( R 2 = .13). Although hope positively influenced school climate for both groups, happiness and resilience were uniquely influential. We discuss considerations for classroom l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The idea is the same for the noise variable as well. Lenz et al (2021) found that noise disrupted students' concentration while doing cognitive tasks like math. Online students have the same challenges, owing to the increased level of background noise and other distractions at their residences.…”
Section: Discussionmentioning
confidence: 99%
“…The idea is the same for the noise variable as well. Lenz et al (2021) found that noise disrupted students' concentration while doing cognitive tasks like math. Online students have the same challenges, owing to the increased level of background noise and other distractions at their residences.…”
Section: Discussionmentioning
confidence: 99%
“…School counselors are tasked with fostering student resilience as well as increasing other internal capacities (Lenz et al., 2021; Roche et al., 2020; Zyromski et al., 2022). A growing number of studies have evaluated the effectiveness of ASE‐informed social‐emotional learning (SEL) interventions aimed at improving the internal capacities of students to overcome adversities and improve their success in schools (Bowers et al., 2022; Ceballos et al., 2021; Lemberger‐Truelove et al., 2018; Lemberger‐Truelove et al., 2020; Webb et al., 2019).…”
Section: Prevention Program Development To Address Sdomh Influencementioning
confidence: 99%
“…School counselors can instill hope leading to resilience by helping students connect with other local youth or adults engaged in efforts to mitigate risks to the environment and address the psychological and emotional stress associated with climate change. Implementing these positive psychology constructs such as hope and resilience into the school counseling vision and mission statements can also help create a positive school climate (Lenz et al, 2021). Pajares's (2006) work on self-efficacy emphasized the value of vicarious experiences of youth in observing social models (parents and teachers) or peers (those with similar abilities) successfully identifying and completing tasks.…”
Section: Recommendation 1: Addressing Eco-anxietymentioning
confidence: 99%